The role of host country institutions and firm factors on the internationalization process of emerging market multinationals entering in developed and developing countries. - Chueke, Gabriel Vouga (2018)
This Ph.D. dissertation aims to identify the determinant factors that influence the choice of Emerging Market Multinational Enterprises (EMNEs) to carry out a greenfield investment or an acquisition in both developing and developed countries. To reach this goal, we proposed a conceptual framework composed of different dimensions related to the firm, industry and host country factors. We grounded our model on concepts derived from institutional theory, transaction cost theory, internationalization theories and studies on entry mode choice. We used several complementary methods such as: exploratory factor analysis, cluster analysis, Manova and binary logistic regression. Moreover, we used an innovative method in international business studies called Qualitative Comparative Analysis (QCA). We collect data from different secondary sources such as OECD, World Economic Forum, World Bank, Brazilian Multinationals Observatory, Bovespa, Orbis database, among others. More than 1,000 Brazilian subsidiaries were identified in more than 50 countries. Preliminary results point to differences between the role of institutions in EMNEs operations in developed and developing countries. It seems that institutions play a relevant role in the internationalization behavior of EMNEs. However, multinationals can develop certain competencies that reduce the level of perceived internal and external uncertainty. In addition, our study findings reveal how each studied dimension contributes in a different way to the choice between performing a greenfield investment or an acquisition.